OPTIMIZING GEOSPATIAL LITERACY: A QUALITATIVE EXPLORATION OF GOOGLE EARTH AS AN EFFECTIVE LEARNING TOOL IN PRIMARY EDUCATION - Ria Indhirawati; Erik Aditia Ismaya; Muh Dliyaul Haq (Sean Institute, 2023)
The utilization of information technology in the field of education, particularly Google Earth, has become a significant breakthrough. This article examines the potential of Google Earth as a map learning tool at SDN Sidomulyo 02. The research focuses on students and teachers from grades 4-6, employing a qualitative approach with a case study. The research results indicate an improvement in student engagement, a better understanding of map concepts, and increased learning motivation. Google Earth provides a dynamic, visual, and interactive experience, allowing students to explore the world virtually. This advantage is evident in the identification of map symbols, understanding legends, and interpreting geographical information. A comparison with conventional methods emphasizes the superiority of Google Earth in the context of map learning, supporting a contextual learning approach. Despite the positive outcomes, challenges in implementation involve a learning curve for teachers. Therefore, advanced training and technical support are key to the effectiveness of Google Earth usage. This article contributes to a deeper understanding of the positive impact of Google Earth on students' geospatial literacy. Its implications include recommendations for teachers and policymakers to integrate learning technologies, especially Google Earth, into elementary education curricula. As a significant contribution, this research paves the way for the broader use of similar technologies in elementary education and serves as a foundation for further research in the development of learning methods that integrate technology.